Neighbourhood Impacts on Wellbeing: The Role of Housing among Low-Income Tenants - Rolfe, Steve (Social Inclusion, 2020)
The existing literature on neighbourhood effects suggests that a number of factors within local areas can have an impact on health, including environmental hazards, social networks and the socio-economic status of the area. However, there is minimal evidence regarding the role of housing organisations in shaping these effects. This article sets out the findings from a three-year longitudinal, mixed methods study of tenants of three housing organisations operating in the social and private rented sectors, examining different aspects of neighbourhood experience and their relationship to health and wellbeing outcomes. The findings demonstrate impacts of the immediate environment in terms of close neighbours, the wider neighbourhood environment, and social support networks, which are heavily influenced by tenant characteristics, previous experience and expectations. The services provided by housing organisations, themselves shaped by regulation and market factors, are also important. The findings will have relevance for tenants, housing providers, public health professionals and policy makers.